2022
DOI: 10.1073/pnas.2207897119
|View full text |Cite
|
Sign up to set email alerts
|

Creative destruction: New protein folds from old

Abstract: Mechanisms of emergence and divergence of protein folds pose central questions in biological sciences. Incremental mutation and stepwise adaptation explain relationships between topologically similar protein folds. However, the universe of folds is diverse and riotous, suggesting more potent and creative forces are at play. Sequence and structure similarity are observed between distinct folds, indicating that proteins with distinct folds may share common ancestry. We found evidence of common ancestry between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…The individual parts readily assemble to form a heterodimer, not just when mixing the individually purified lobes, but also within the cell upon coexpression. While the N-and C-terminal lobes appear to be stable and well-behaved proteins on their own, formation of the heterodimer almost completely restores the characteristics of the full-length RBP, confirming the importance of interdomain interactions on the evolution, stability and function of the PBP fold, similarly to what has been reported for other multidomain proteins (Alvarez-Carreño et al, 2022;Han et al, 2007;Vogel et al, 2004).…”
Section: Implications For the Evolution Of The Pbp Fold And Protein E...supporting
confidence: 80%
See 1 more Smart Citation
“…The individual parts readily assemble to form a heterodimer, not just when mixing the individually purified lobes, but also within the cell upon coexpression. While the N-and C-terminal lobes appear to be stable and well-behaved proteins on their own, formation of the heterodimer almost completely restores the characteristics of the full-length RBP, confirming the importance of interdomain interactions on the evolution, stability and function of the PBP fold, similarly to what has been reported for other multidomain proteins (Alvarez-Carreño et al, 2022;Han et al, 2007;Vogel et al, 2004).…”
Section: Implications For the Evolution Of The Pbp Fold And Protein E...supporting
confidence: 80%
“…It has been previously suggested that this common ancestor could have been a CheY-like protein adopting a flavodoxin-like fold. Formation of an ancestral dimer in combination with a gene duplication and fusion event might have led to the typical bilobal structure of the modern PBP (Figure 1a), an event that has already been investigated for the evolution of other protein folds (Alvarez-Carreño et al, 2022;Farías-Rico et al, 2014;Toledo-Patiño et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins with conserved secondary structures have also been shown to assume different tertiary arrangements. [ 26,75,76 ] Furthermore, new protein folds can evolve by gene fusion in a process known as “creative destruction.” [ 77 ] In this process, a fused polypeptide can combine conserved elements of secondary or supersecondary structure in new ways while the remainders of the ancestral folds are destroyed.…”
Section: Evidence For Fluid Fold Spacementioning
confidence: 99%
“…The transition of a protein sequence from one fold to another, whether it be nearby (A → B) or more distant (A → C), and be it naturally (via evolution) or artificially (via design/engineering), likely occurs over multiple intermediate steps. These mechanistic steps include processes such as combining or permuting short secondary structural segments or longer regions (such as whole secondary structural elements [SSEs]), or mutating individual residues via nonsynonymous substitutions [5,[13][14][15][16]. In general, each such step may yield a new 3D structure, and that structure may correspond to the same or a different 'fold'.…”
Section: Fold Space Structural Transitions and Protein Fragmentsmentioning
confidence: 99%